QuEChERS Method Followed by Solid Phase Extraction Method for Gas Chromatographic-Mass Spectrometric Determination of Polycyclic Aromatic Hydrocarbons in Fish - Mona Khorshid; Eglal R. Souaya; Ahmed H. Hamzawy; Moustapha N. Mohammed (International Journal of Analytical Chemistry)
A gas chromatography equipped with mass spectrometer (GCMS) method was developed and validated for determination of 16 polycyclic aromatic hydrocarbons (PAHs) in fish using modified quick, easy, cheap, effective, rugged, and safe (QuEChERS) method for extraction and solid phase extraction for sample cleanup to remove most of the coextract combined with GCMS for determination of low concentration of selected group of PAHs in homogenized fish samples. PAHs were separated on a GCMS with HP-5ms Ultra Inert GC Column (30 m, 0.25 mm, and 0.25 µm). Mean recovery ranged from 56 to 115%. The extraction efficiency was consistent over the entire range where indeno(1,2,3-cd)pyrene and benzo(g,h,i)perylene showed recovery (65, 69%), respectively, at 2 µg/kg. No significant dispersion of results was observed for the other remaining PAHs and recovery did not differ substantially, and at the lowest and the highest concentrations mean recovery and RSD% showed that most of PAHs were between 70% and 120% with RSD less than 10%. The measurement uncertainty is expressed as expanded uncertainty and in terms of relative standard deviation (at 95% confidence level) is ±12%. This method is suitable for laboratories engaged daily in routine analysis of a large number of samples.